Hypervirulent Klebsiella pneumoniae in California Sea Lions (Zalophus californianus): Pathologic Findings in Natural Infections. (September 2017) - Seguel, Mauricio; Gottdenker, Nicole L.; Colegrove, Kathleen; Johnson, Shawn; Struve, Carsten; Howerth, Elizabeth W.
Tissues of stranded California sea lions ( Zalophus californianus ) naturally infected with a hyperviruluent strain of Klebsiella pneumoniae were examined by histopathology and immunohistochemistry against the K. pneumoniae K2 capsular antigen. In 7 of 8 animals, there was severe purulent bronchopneumonia, sometimes complicated by fibrinonecrotizing pleuritis with pyothorax. In affected areas of lung, large numbers of degenerate neutrophils and macrophages were admixed with rare large extracellular and intracellular gram-negative bacilli surrounded by a prominent capsule. Through serotyping, polymerase chain reaction, sequencing, and immunohistochemistry, these bacteria were confirmed to be a K2 serotype of K. pneumoniae. The same bacteria were identified through double immunolabeling within macrophages in blood vessels, lymph nodes, spleen, and liver. Intact K. pneumoniae were identified on epithelial surfaces of the nasopharyngeal, tracheal, and small intestine mucosae and within distal renal tubules. Our findings indicate that hypervirulent K. pneumoniae causes severe respiratory disease and intrahistiocytic bacteremia in California sea lions.